100 Soruda Yabancı Dil Olarak Türkçe Öğretimi - Acemoğlu, Adil; Oryaşin, Utku; Güven, Ahmet Zeki; Okur, Alpaslan; Demirdöven, Gökhan Haldun; Bölükbaş Kaya, Fatma; Demirel, Mehmet Volkan; Özden, Esra; Akkaya, Mehmet; Şengül , Ladin; Dönmez, Ayhan; İşci Karameşe, Cenan and Bal, Mazhar and Öz, Koray and Türkel, Ali and Çıvğın, Hakan and Kırmızı, Fatma and Özdemir, Serpil and Aydın, İbrahim Seçkin (Academician Publishing Book DOI Portal, 2023)
-